An investigation of whether emotion regulation mediates the relationship between attachment insecurity and suicidal ideation and behaviour. (29th March 2022) - Turton, Holly; Berry, Katherine; Danquah, Adam; Green, Jessica; Pratt, Daniel
Abstract: Objective: The aim of this research was to examine relationships between attachment insecurity and suicidal ideation and behaviour. Secondary aims were to explore the mediating role of emotion dysregulation and the moderating role of betrayal trauma in explaining hypothesised relationships. Method: Sixty‐five participants with experience of suicidal ideation completed questionnaire measures assessing attachment security, suicide ideation, emotion regulation, betrayal trauma, depressive symptoms and hopelessness. Results: A direct relationship was found between avoidant attachment and suicide ideation after controlling for age and gender. Multiple suicide attempters had higher anxious attachment. Anxious and avoidant attachment, suicide ideation and betrayal trauma were associated with emotion dysregulation. The relationship between attachment insecurity and suicide ideation was not mediated by emotion dysregulation. In the mediation model, only anxious attachment remained a significant predictor of emotion regulation and there was no significant effect of emotion regulation nor betrayal trauma, on suicide ideation. Conclusion: Suicidal individuals may benefit from therapeutic intervention that explores attachment‐related difficulties and therapies such as dialectical behavioural therapy, which support skills in emotional regulation. Future longitudinal research should identify other important mediators of the association between attachment and suicidality to develop more targeted psychological interventions for suicidality.